Revitalizing the Values of Mercy Education Through Religious Education Learning in the National Curriculum in Indonesia - Nasir, Abdul Hafidz (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The values of mercy education become the teachings of every religion. However, these values have not been able to be realized in the daily life of students. This study aims to analyze whether the values of mercy education for each religion are the content of the religious education curriculum in schools, how the problems faced in instilling these love values in students, and how the revitalization efforts will be in the future. The research method used is literature research. Data collection techniques use documentation. The collected data were analyzed using critically performed text analysis. The results showed: First, the curriculum of religious education in schools for all religions in Indonesia has contained the value of love, albeit with different sequences. Second, the problem faced is that internalizing the value of love for students has not been appropriately realized because the method used is not appropriate. Third, instilling the value of love in students in religious learning needs to be revitalized by applying more effective learning methods. Three methods are considered effective for instilling the value of love in students: habituation, exemplary, and reflective learning methods. The results showed that learning the value of love and affection in schools is only limited to recognition and this shows that learning is only focused on knowledge/cognitive aspects without paying attention to the attitude/love aspect. Therefore, it is necessary to revitalize the cultivation process by applying more effective learning methods such as habituation, reflective, and exemplary learning.